How to prevent food poisoning : - Scott, Elizabeth (John Wiley, 1998)
How to Prevent Food Poisoning gives you the facts, figures, and information you need to safeguard your family's health. From the many different causes and complications of food poisoning to workable guidelines that are practical and easy to follow, this unique guide gives you everything you need to select, prepare, and store food without risk or worry. Here are the right ways to: Be sure the food you're buying is safe; Prevent food contamination in your home; Transport and store food properly — including leftovers; Eat safely in restaurants; Reduce germs in the kitchen.